1987
DOI: 10.1128/jb.169.8.3809-3813.1987
|View full text |Cite
|
Sign up to set email alerts
|

Transductional analysis of chloramphenicol biosynthesis genes in Streptomyces venezuelae

Abstract: Auxotrophs isolated from two chloramphenicol-nonproducing mutants of Streptomyces venezuelae included three requiring pyridoxal (Pxl-), VS248 (cml-11 pdx-2), VS253 (cml-11 pdx-3), and VS258 (cml-12 pdx-4), and one requiring thiosulfate, VS263 (cml-12 cys-28). Results of SV1-mediated transductions were consistent with the relative marker order cys-28-cml-12-cml-11-pdx-2,3,4,5, all of which were cotransducible and must therefore span less than 45 kilobases of DNA, the approximate length of DNA packaged by SV1. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 5 publications
(6 reference statements)
2
17
0
Order By: Relevance
“…3). This location for tyr-2 is consistent with its earlier map assignment between hisA6 and thrC1 (Chaliciopoulos, 1985;Vats et al, 1987), and is comparable with that of tyrA,B in S. coelicolor A3(2) (Hopwood & Kieser, 1990). In crosses with VS161, which carries the tyr-2 marker, no segregation was observed between tyr-2+ and tsr of AP41; other markers in each cross segregated independently.…”
Section: Chromosomal Location Of Trpegsupporting
confidence: 75%
“…3). This location for tyr-2 is consistent with its earlier map assignment between hisA6 and thrC1 (Chaliciopoulos, 1985;Vats et al, 1987), and is comparable with that of tyrA,B in S. coelicolor A3(2) (Hopwood & Kieser, 1990). In crosses with VS161, which carries the tyr-2 marker, no segregation was observed between tyr-2+ and tsr of AP41; other markers in each cross segregated independently.…”
Section: Chromosomal Location Of Trpegsupporting
confidence: 75%
“…Consistent with these expectations, Brown et al (1996) demonstrated that Cm production in Streptomyces venezuelae ISP5230 was severely impaired when an indigenous gene that complemented a Streptomyces lividans pab mutant was replaced with a disrupted allele. The locus has not yet been genetically linked to the mapped Cm biosynthesis gene cluster in S. venezuelae ISP5230 (Doull et al, 1986 ;Vats et al, 1987), but the DNA that complemented the S. lividans pab lesion has been shown by cloning and sequence analysis to be a gene consisting of fused pabA and pabB domains. In their deduced amino acid sequences, these domains closely resemble the products of discrete pabA and pabB genes in a variety of bacteria (Brown et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Those for chloramphenicol are flanked by the auxotrophic markers pdx-4 and cys-28 (Doull et al, 1986 ;Vats et al, 1987 ;Stuttard, 1988). Our initial interest in the cys-28 marker led us to explore the molecular biology and biochemistry of cysteine biosynthesis in Str.…”
Section: Filamentous Bacteria Of the Genusmentioning
confidence: 99%
“…venezuelae ISP5230 (Vats et al, 1987) was examined for growth requirements imposed by the unidentified cys-28 mutation. When colonies on MM agar were supplemented with substances potentially involved in cysteine biosynthesis, positive responses were obtained with cysteine, methionine, homocysteine and cystathionine (Table 2).…”
Section: Test For Complementation Of the Cys-28 Mutation With Orf1mentioning
confidence: 99%